The Origin and Evolution of the I.L.O. and Its Role in the World Community - Morse, David A. (Ithaca: New York State School of Industrial and Labor Relations, Cornell University, 1969)
This publication is chiefly a history of the I.L.O. (International Labor Organization).The I.L.O was established fifty years ago under the League of Nations, and has continued to serve the world as one of the specialized agencies of the United Nations. It has a unique structure, with tripartite representation from the participating nations; that is, with labor, management, and government representatives.
Includes indexes.
Bibliography: p. 115-117.
ne 20/03/2018
Loan
Keywords: International Labor Organization